Marketing Communication Strategies Through Social Media Content to Increase Brand Awareness on ESS Coffeeshop - Septihani, Aulia; Sari, Yunita; Santoso, Prasetya Yoga (International Journal of Marketing & Human Resource Research, 2025)
Digital technology has transformed how businesses communicate with their consumers, particularly in the food and beverage (F&B) industry. One of the key strategies to enhance brand awareness is marketing communication via social media. This study aims to analyze marketing communication strategies through Instagram content to increase brand awareness, with a case study on Coffeeshop ESS. This research employs a qualitative approach, utilizing data collection techniques such as interviews, observations, and content analysis of social media platforms. The findings indicate that ESS leverages various Instagram features, including feed posts, stories, reels, and IGTV, to engage with its audience. The marketing strategies implemented include consistent branding, engaging storytelling, collaboration with influencers, and interactive promotional activities. However, challenges such as intense competition in the F&B industry and changing social media algorithms affecting content reach remain significant. The study concludes that an effective digital marketing communication strategy can enhance brand awareness and customer engagement. Recommendations from this research include optimizing visual content, leveraging social media trends, and increasing customer interaction to maintain brand loyalty.